Reputation: 161
I was wondering how the following code evaluates to 15.
((lambda(x y) (+ (x * y) (x + y))) (lambda (a b) (a b b)) 3)
I have been looking at it for a while and cannot seem to understand why the evaluation does not result in an error. Could someone provide a detailed step by step instruction on how this evaluates to 15?
Upvotes: 1
Views: 80
Reputation: 2789
Perhaps it is easier to see what is happening if you named the lambdas. For example,
(define (f x y)
(+ (x * y) (x + y)))
(define (g a b)
(a b b))
Then the expression ((lambda (x y) (+ (x * y) (x + y))) (lambda (a b) (a b b)) 3)
becomes:
(f g 3)
and it evaluates as:
(f g 3)
=> (+ (g * 3) (g + 3))
=> (+ (* 3 3) (+ 3 3))
=> (+ 9 6)
=> 15
Upvotes: 4